Selection of Renewable Energy Sources for Sustainable Development of Electricity Generation System using Analytic Hierarchy Process: A Case of Malaysia - Salman, Ahmad; Razman, Mat Tahar (Elsevier, 2014)
Currently, around 90% of Malaysia's electricity generation depends on fossil fuels. This reliance, in a long run, is not a secure option. However, renewable energy sources can contribute to a sustainable electricity generation system; but diversifying fuel supply chain is a complex process. Therefore, the aim of this paper is two folds. Firstly, various renewable resources potential are reviewed, and secondly an assessment model is developed for prioritizing renewable options. Four major resources, hydropower, solar, wind, biomass (including biogas and municipal solid waste) are considered. Their electricity generation potential, along with any likely shortcoming is also discussed. Moreover, using a multi-perspective approach based on analytic hierarchy process (AHP), an assessment model is developed. AHP model employs four main criteria, technical, economical, social and environmental aspects, and twelve sub-criteria. From the review it was found that renewable resources seem to have a sufficient potential to develop a sustainable electricity system. Furthermore, AHP model prioritize those resources, revealing that solar is the most favorable resource followed by biomass. Hydropower and wind however, are ranked third and fourth, respectively. The model also shows that each resource is inclined towards a particular criterion; solar towards economical, biomass towards social, hydropower towards technical, and wind towards environmental aspect. Besides reporting AHP model for the first time in Malaysian context, the assessment performed in this study, can serve decision makers to formulate long-term energy policy aiming for sustainability.